Perubahan Paradigma Dalam Penyusunan Rencana Detail Tata Ruang Yang Berkelanjutan Dan Menjamin Kepastian Hukum Pasca Politik Hukum Cipta Kerja Di Indonesia - Priyanta, Maret; Zulkarnain, Cut Sabina Anasya (UI Scholars Hub, 2024)
The amendment to the RDTR enactment in Law Number 6 of 2023 concerning the Enactment of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into Law is aimed at ensuring the essence of hierarchy and the operationalization of general plans runs in accordance with the concept of plan hierarchy. Previously, equality of enactment forms were applied by the principle of lex specialis derogat legi generalis, which essentially caused the RDTR to be able to correct RTRW content material due to the equality of the enactment forms. In practice, the synergy of the position and content of the two plans above as general plans (RTRW) and detailed plans (RDTR) which are tiered and complementary cannot be realized by just a formal legal process through its enactment as regional head regulations. In this case, the legal material for its preparation is realized through a paradigm shift in the preparation of the RDTR which can no longer be a form of exercising full discretion by the Regional Government regarding the resolution of spatial planning problems and its contents cannot be contradictory with the RTRW. This research uses a normative juridical approach. In this case, a descriptive-analytical method is used with a comprehensive holistic approach. This research aims to determine and conclude the position of RDTR after the Job Creation Law in spatial planning. In this case, it is necessary to improve the quality of the preparation practice of the RTRW as a general plan, both in terms of material content and legal political processes and improve the quality of the preparation of the RDTR by accommodating dynamic and operational arrangements for the strategic policies that have been regulated in the RTRW.